Educational challenges facing prisoners at Kutama-Sinthumule Correctional Centre: a case study of grade twelve (12) young adult learners - Mathebula, Nkarhi Excellent (University of Limpopo, 2014)
This mini-dissertation is about educational challenges facing grade twelve (12) young adult prisoners at Kutama-Sinthumule Correctional Centre. It is a study of grade twelve (12) learners. The aim of the study is to get an insight into educational challenges facing grade twelve (12) young adult learners at Kutama-Sinthumule Correctional Centre. This study has attempted to contribute towards solutions to educational challenges facing grade twelve (12) young adult learners at Kutama-Sinthumule Correctional Centre. The management of Kutama-Sinthumule and the Department of Correctional Services were made aware of the problems that young adult prisoners face while doing grade twelve (12) in that prison. In order to achieve the aims outlined above, I formulated the following main research question: What are the educational challenges facing grade twelve (12) young adult Prisoners at Kutama-Sinthumule Correctional Centre? I tried to answer the question outlined above by undertaking an explorative study which has elements of needs assessment and case study. I have decided to undertake an explorative study because very little is known about educational challenges facing prisoners prior to this research. Since the study has elements of needs assessment, the situation of grade twelve (12) young adult prisoners and values of an education system with desired outcomes was looked against. The needs are stated by grade twelve (12) learners; their educators; their facilitators; and the coordinator of the programme in relation to the system. I have decided to select grade twelve (12) learners at Kutama-Sinthumule Correctional Centre as my case. There are other educational programmes at Kutama-Sinthumule Correctional Centre, but I have decided to concentrate on a grade twelve programme. I have decided to undertake a case study because a case study promotes a better understanding of a practice or issue and facilitates informed decision making. Chapter two outlines the theoretical framework of the study. I began chapter two by defining important concepts. The concepts such as Prisoner; Prison; and Young Adult are defined thoroughly. I formulated assumptions about what could be educational challenges facing grade twelve (12) young adult learners at Kutama-Sinthumule Correctional Centre. I read documents and conducted exploratory interviews with grade twelve learners, educators and other role players at Kutama-Sinthumule, hence I identified the following educational challenges facing grade twelve (12) learners at the Correctional Centre: lack of access to the internet; lack of resources; lack of motivation; communicating in the medium of instruction; shortage of better trained staff; overcrowded classrooms; insufficient study time; duration of the programme; shortage of staff; and insufficient time allocated to lessons. In chapter three, I describe the design of the study. The main focus of this chapter was to discuss the two routes of data collection. The first route had to do with reviewing relevant documents from the Department of Correctional Services and operational policies and procedures at Kutama-Sinthumule Correctional Centre. The second route has to do with the data that has been collected in the field using different data collection instruments. How data has been analyzed using a data matrix is also shown in this chapter. The chapter concludes by presenting ethical considerations. Chapter four begins by highlighting the setting of the study. It goes on to describe the town of Louis Trichardt where Kutama-Sinthumule Correctional Centre is situated. It further gives a brief history of the town. The Climate, Geography, Demography, Population, Key Statistics, Name change, and Economy are outlined in this chapter. This chapter also presents the findings of the study. I have also outlined in detail the views of the interviewees in relation to the critical factors of this study. A description of subjects offered for this grade twelve programme is done in this chapter. The chapter concludes by discussing the findings of this study. Chapter five presents the final recommendations, conclusion, and reflections of this study. This chapter harmonizes information from all the previous chapters in discussing educational challenges facing grade twelve (12) young adult prisoners at Kutama-Sinthumule Correctional Centre. The chapter also suggests possible solutions to these educational challenges facing grade twelve (12) young adult learners at Kutama-Sinthumule Correctional Centre. The chapter concludes by making recommendations for furtherstudy, as education and its related challenges in the prisons seems to be under-researched, particularly for grade twelve (12) young adult learners.
Thesis (MEd. (Adult Education)) --University of Limpopo, 2014
Keywords: Educational challenges; Prisoners; Kutama-Sinthumule Correctional Centre; Grade 12 young prisoner learners; 374; Prisoners - Education; Prisoners - Education - Law and legislation; Adult education - South Africa - Limpopo Province